Характеристика окремих функції професійної правосвідомості - Куренда, Л.; Kurenda, L. (Східноєвропейський національний університет імені Лесі Українки, 2013)
У статті здійснено аналіз функцій професійної правосвідомості стосовно сфер юридичної практики або певних груп юристів-професіоналів, які вирізняються стосовно виконуваних ними функцій і змісту їхньої праці (слідчих, прокурорів, адвокатів, юрисконсультів, нотаріусів та ін.). Досліджено погляди провідних учених, котрі вивчали окремі аспекти функцій професійної правосвідомості, і на цій основі запропоновано власну їх класифікацію. In the article the functions of justice by professional fields of law practice or certain groups of professional lawyers who excel in terms of the functions they perform and content of their work (investigators, prosecutors, advocates, solicitors, notaries, etc.) are analyzed. On the basis of the analysis of views of scientists, who have studied some aspects of the professional sense of justice, the author makes her own conclusion it is advisable to highlight the following features of lawyer’s legal consciousness, specifying its nature, objectives and purpose: the function of generating individual legal concepts, the function of the developing a feeling of right and fairness, and the function of ensuring the freedom of taking decisions, and the function of the development the activity in the work, the function of the professionally of legal thought formation, the function generation professional habits, legal negligence warning function and the function of providing gaps in the legislation.
The Characteristics of the Individual Functions of Professional Sense of Justice
Keywords: право; функції; правосвідомість; професія; поведінка; орієнтація; law; functions; sense of justice; profession; conduct; orientation